1993
DOI: 10.1038/sc.1993.92
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cardiac dysrhythmias in chronic spinal cord injury patients

Abstract: The incidence of cardiac dysrhythmias is characterized in a group of 47 chronic SCI patients (greater than 30 days post injury; range 35-3605 days) with SCI lesions ranging from C4 to L3 who were referred for evaluation of a potential cardiac dysrhythmia by 24 hour Holter monitoring. Patients were grouped according to level of injury as paraplegic (T1 and below), n = 22, or quadriple gic (C3-C8), n = 25. No evidence of life threatening dysrhythmias was noted in either group, and no differences were evidenced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 6 publications
1
13
0
1
Order By: Relevance
“…A propensity toward dysrhythmias has been documented acutely after SCI, 24 though it has not been shown that chronic SCI is associated with dysrhythmia in the absence of underlying CHD. 25 While dysrhythmia could be associated with heightened cerebrovascular disease risk, the reason why valvular disease is elevated according to level and Frankel/ASIA grade is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A propensity toward dysrhythmias has been documented acutely after SCI, 24 though it has not been shown that chronic SCI is associated with dysrhythmia in the absence of underlying CHD. 25 While dysrhythmia could be associated with heightened cerebrovascular disease risk, the reason why valvular disease is elevated according to level and Frankel/ASIA grade is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is known from previous studies that at rest, individuals with SCI have a higher incidence of nonspecific ST elevation (and thus early repolarization) than do ablebodied individuals (6,7), and they are also reported to be at increased risk of developing ECG abnormalities, such as premature atrial contractions, intraventricular conduction delays, and bundle-branch blocks (2,3). Several studies have indicated that the incidence of arrhythmia in patients with SCI (particularly bradyarrhythmias) is increased and that those with higher lesions are more at risk of developing bradyarrhythmias (9).…”
Section: Cardiovascular Control During Vibrostimulationmentioning
confidence: 99%
“…However, the reasons for this are uncertain. It may be that SCI increases the risk of unstable blood pressure and cardiac arrhythmias (2)(3)(4)(5) or other electrocardiographic (ECG) abnormalities (6,7) that may predispose patients to adverse cardiac events. Most previous studies examining the incidence of cardiac arrhythmias in SCI patients have been performed while the subject was in the resting state (2,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition to hemodynamic abnormalities, SCI can lead to cardiac arrhythmia including sinus bradycardia, supraventricular arrhythmia, ventricular arrhythmia and cardiac arrest. [5][6][7][8] Although these cardiac arrhythmias are relatively well recognized in the subacute and chronic stages after SCI, there is a paucity of studies focused on abnormal cardiac electrical activity during the early stages following SCI.…”
Section: Introductionmentioning
confidence: 99%